The influence of fashion trends on the acquisition of sustainable textiles (ModaPalavra e-periódico, 2023)
The purpose of the study is based on the premise of reflecting on how the process of choice for purchasing sustainable fashion trend products happens among designers. The research is defined as qualitative and is part of a case study of Bureaux UseFashion, focusing on design trends, aesthetics applied to textile articles for winter 2022, and the main aesthetic attributes in the development of design projects using textile articles. The study was conducted with the aim of providing theoretical support to assist in the development of sustainable design choice processes and how to transparently communicate such choices to the consumer public.
Keywords: trends in fashion; aesthetics; sustainable textiles